Kānphatthanā khrư̄akhāi čhit ʻāsā phư̄a phatthanā sukkhaphāp læ khunnaphāp chīwit chumchon : botsangkhro̜ čhāk kānkhapkhlư̄an khrōngkān wičhai - Wirat Khamsīčhan (Sathāban Phatthanā Sukkhaphāp ʻĀsīan, Mahāwitthayālai Mahidon, 2011)
Research on community participation in the development of health and social conditions in Thai communities.